An overview of non-cystic fibrosis bronchiectasis - Smith, Maeve P. (Henry Stewart Talks, 2013)
Non-cystic fibrosis bronchiectasis, A vicious cycle of chronic airways infection and inflammation, Significant clinical and socioeconomic morbidity, Crucial to try to establish and treat any underlying aetiology, Disease severity should be assessed, Long term management is multifaceted and includes airway clearance techniques, anti-inflammatory strategies and antimicrobial strategies